2021
DOI: 10.1007/s41999-021-00486-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19: urging a need for multi-domain assessment of COVID-19 inpatients

Abstract: Key summary points Aim To retrospectively analyse data obtained from the multi-domain assessment of hospitalized COVID-19 patients, to describe their health status at discharge, and to investigate whether subgroups of patients, more specific ICU patients and older adults (> 70 years), had more (or less) risk to experience specific impairments. Findings The results of the assessment show that physical, functional, cognitive, nutritional, and psychological im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
3
24
0
1
Order By: Relevance
“…The older patients were more cognitively impaired than the younger patients ( Table 2 ). This finding is in line with what might be expected in an elderly population and what was seen in a previous study of COVID-19 patients [ 30 ], as well as what has been described by the Pan American health organization [ 6 ]. Although the total study sample scored below the 26-point cutoff on the MoCA, no difference in the level of cognition was seen based on admission to the ICU.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The older patients were more cognitively impaired than the younger patients ( Table 2 ). This finding is in line with what might be expected in an elderly population and what was seen in a previous study of COVID-19 patients [ 30 ], as well as what has been described by the Pan American health organization [ 6 ]. Although the total study sample scored below the 26-point cutoff on the MoCA, no difference in the level of cognition was seen based on admission to the ICU.…”
Section: Discussionsupporting
confidence: 93%
“…The PCFS scores indicated that the patients themselves expressed difficulties managing daily activities, although they were able to take care of themselves. For both the ICU treated patients and the older group, the BI was in line with what has been previously shown in hospitalized COVID-19 patients, being somewhat dependent after hospitalization [ 17 , 18 , 22 , 30 ]. In particular, this suggests that older patients and ICU-treated patients require further follow-up after hospital discharge.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results may be useful in selecting appropriate candidates for rehabilitation during hospitalization from limited rehabilitation resources to treat and prevent functional decline and to provide the high-risk patient families or caregivers with sufficient time to arrange support after the discharge home (e.g., home help services and a reclining bed for easy transferring from a bed). These implications would be supported by a previous study, which showed that multi-domain assessment of COVID-19 inpatients, including functional, physical, and cognitive assessment, may be useful for evaluating their health status and for planning care, rehabilitation, and follow-up after discharge [17].…”
Section: Discussionmentioning
confidence: 62%